pls i need help with it

Step-by-step explanation: Adding and Subtracting Rational Expressions
3. [tex]\frac{2a}{4b} + \frac{3}{4b} = \frac{2a + 3}{4b}[/tex]
4. [tex]\frac{2y}{5x^{2}} - \frac{3x}{4xy} = \frac{8y^{2}}{20x^{2}y} - \frac{15x^{2}}{20x^{2}y}[/tex]
[tex]\frac{8y^{2}}{20x^{2}y} - \frac{15x^{2}}{20x^{2}y} = \frac{8y^{2} - 15x^{2}}{20x^{2}y}[/tex]
5. [tex]\frac{7}{m - 6} - \frac{1}{m} = \frac{7m}{m(m - 6)} - \frac{m - 6}{m(m - 6)}[/tex]
[tex]\frac{7m}{m(m - 6)} - \frac{m - 6}{m(m - 6)} = \frac{6m - 6}{m(m - 6)}[/tex]